Identification of stroke biomarkers using proteomic profiling of extracellular vesicles derived from human blood: a preliminary study - Tae Yeon Kim; Jae Yeon Park; Yun Seo Cho; Dong Hyuk Youn; Sung Woo Han; Harry Jung; Yong-Jun Cho; In cheol Jeong; Jin Pyeong Jeon; Kangeun Ko; Hyo Youl Moon; Hyo Youl Moon; et al. (Frontiers in Neurology, 2025)
IntroductionStroke is a devastating brain disease that causes extensive neurological impairment and high mortality. Rapid diagnosis and intervention of stroke are necessary to minimize neurological damage and improve recovery. Extracellular vesicles (EVs) have been identified as potential biomarkers for stroke, suggesting promising avenues for rapid diagnosis and prognostic assessments.MethodsThis preliminary study aimed to evaluate the potential of EVs as biomarkers in the distinct pathophysiological mechanisms of hemorrhagic stroke (HS) and ischemic stroke (IS). We have identified proteins differentially expressed in EVs derived from the blood of HS and IS patients. EVs were isolated using an isolation kit, followed by proteomic analysis by LC-MS/MS to compare protein expression patterns.ResultsAs a result, 15 proteins were upregulated and 4 downregulated in HS-derived EVs, and 14 proteins were upregulated and 5 downregulated in IS-derived EVs. Among these, 14 proteins were commonly upregulated and 1 protein was commonly downregulated in both stroke types, whereas the remaining proteins exhibited stroke-type-specific expression patterns. To further explore the proteomic findings, we confirmed the increased levels of CRP and PF4 in HS patients using ELISA, verifying their elevation in patient blood samples.DiscussionAlthough this additional evaluation was conducted only for HS, these findings suggest that EV-derived proteins have potential as biomarkers for both HS and IS, supporting their broader applicability in stroke diagnosis.